2019
DOI: 10.1038/s41598-019-42268-w
|View full text |Cite
|
Sign up to set email alerts
|

β-carboline biomediators induce reveromycin production in Streptomyces sp. SN-593

Abstract: The biosynthetic potential of soil-dwelling actinomycetes to produce diverse bioactive molecules that are useful as drug seeds has been achieved in the laboratory by modifying culture conditions. Availability of a small molecule that can induce secondary metabolism in these microbes can greatly facilitate the exploration of bioactive natural products. In this manuscript, through the screening of natural products and chemical modification, we demonstrated that the presence of the β-carboline compound, BR-1, enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Interestingly, the equilibrium affinity constant of 1.31 μM calculated for BR-1 was almost identical to its bioactive concentration (Fig. S4B) 28 . Additionally, we have found that the tetrahydro form of BR-1 (3) ( Fig.…”
Section: Revu As the Molecular Target Of Br-1mentioning
confidence: 57%
See 4 more Smart Citations
“…Interestingly, the equilibrium affinity constant of 1.31 μM calculated for BR-1 was almost identical to its bioactive concentration (Fig. S4B) 28 . Additionally, we have found that the tetrahydro form of BR-1 (3) ( Fig.…”
Section: Revu As the Molecular Target Of Br-1mentioning
confidence: 57%
“…Additionally, we have found that the tetrahydro form of BR-1 (3) ( Fig. 1) did not induce the production of RMs 28 . As expected, the sensorgram for 3 did not reach saturation at a concentration of up to 87 μM, indicative of non-specific binding (Fig.…”
Section: Revu As the Molecular Target Of Br-1mentioning
confidence: 79%
See 3 more Smart Citations